2007
DOI: 10.2169/internalmedicine.46.0066
|View full text |Cite
|
Sign up to set email alerts
|

Asian Variant of Intravascular Lymphoma: Aspects of Diagnosis and the Role of Rituximab

Abstract: Objective The Asian variant of intravascular lymphoma (AIVL) is a rare non-Hodgkin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 31 publications
0
18
1
Order By: Relevance
“…It should be considered as uncommon that this Asian variant IVLBCL patient initially showed neurological symptoms. The poor prognosis of IVLBCL might be partially related to frequent delays in diagnosis due to its non-specific nature, although survival rates have been shown to increase in those patients who undergo rituximabcontaining chemotherapies (2,3). It has been previously reported that random skin biopsies, regardless of the presence or absence of skin lesions, were comparably sensitive to bone marrow biopsy in the diagnosis of IVLBCL (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be considered as uncommon that this Asian variant IVLBCL patient initially showed neurological symptoms. The poor prognosis of IVLBCL might be partially related to frequent delays in diagnosis due to its non-specific nature, although survival rates have been shown to increase in those patients who undergo rituximabcontaining chemotherapies (2,3). It has been previously reported that random skin biopsies, regardless of the presence or absence of skin lesions, were comparably sensitive to bone marrow biopsy in the diagnosis of IVLBCL (10).…”
Section: Discussionmentioning
confidence: 99%
“…As IVLBCL is thought to be an aggressive lymphoma in the clinical setting, making a timely diagnosis is extremely important since prompt treatment can improve the clinical outcome (2)(3)(4). However, no standard procedure for the diagnosis of IVLBCL has yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…IVL is classified as DLBCL subtype, according to the new WHO classification (17). IVL is characterized by intravascular proliferation of malignant lymphomatous cells, which frequently invade the central nervous system (CNS), skin, lungs and kidneys (12,18,19). Both pituitary and adrenal involvement are frequent in IVL patients (12,20,21).…”
Section: A) B)mentioning
confidence: 99%
“…It often takes an aggressive clinical course and it has been recently known that rituximab is effective for IVL. The Asian variant of intravascular lymphoma (AIVL), which is mainly seen in Asian countries and may be complicated by hemophagocytic syndrome, should also be considered as another differential diagnosis (18,19,22). AIVL takes an exceedingly rapid clinical course as seen in IVL and (R)-CHOP is effective in some cases of AIVL.…”
Section: A) B)mentioning
confidence: 99%
See 1 more Smart Citation